Department of Agricultural Economics; University of Dschang, West Region, Cameroon P O Box: 222 FASA Tchumela Tchoupua Cédric University of Dschang, Cameroon - Sari Anggarawati; Yunus Arifien; Dyah Budibruri Wibaningwati (Agricultural Science, 2020)
The disaster in Karo District due to the eruption of Mount Sinabung on September 15, 2013 has claimed lives, damage to homes, agricultural land and property. This affected the economic and social conditions of affected farmers, so the government intervened to improve these conditions through a rehabilitation and reconstruction program. The purpose of this study is to compare the economic and social conditions of the community before and after the eruption of Mount Sinabung due to rehabilitation and reconstruction activities and examine community participation in recovery activities. The analytical method uses the non-parametric Wilcoxon Signed Rank Test, with two related samples namely the measurement of conditions before the disaster and after the post-disaster rehabilitation-reconstruction are not mutually free. The results show that the land owned by respondents after the disaster was reduced, but land tenure by respondents increased because they rented land elsewhere. The types and number of livestock have decreased such as buffalos and chickens, but cattle have increased due to the aid in purchasing cattle. Money capital has increased because of the provision of financial assistance from the private sector or government. The number of kiosks and sales turnover increased with the change of the area around the disaster into a tourist destination. Likewise, farm family income has increased with the new arable land in Siosar which is planted with vegetables in addition to the results of coffee on the old land that is ready to harvest. Resilience of respondent faces disaster and willingness to rise from disaster in the category of vulnerable and increasing. Work ethic in the high category increases, but in the medium category it actually decreases. The dependency of aid from the government in the high category increases, but in the low category it decreases.